STUDY COMPERATIVE ASURANSI JIWA ANTARA ASURANSI SYARIAH DAN ASURANSI UMUM - NIRWANA DEWI HARAHAP (JURNAL ILMIAH KOHESI, 2021)
The purpose of general insurance and Sharia insurance in its principle is to shift the risk posed by unexpected events toothers who are willing to take that risk by indemnifying it. Parties who are willing to accept the risk are called insurers. Hewants to do it, of course, not solely for the sake of humanity (maybe even this social reason never existed), but because hesaw in this effort there was a gap to take advantage. As a company, the insurer is however more able to assess themagnitude of the risk than the insured person. Although Islam considers that general insurance is contrary to islamicteachings, it does not mean that there is a possibility of insurance in Islam. Insurance is very important in every human lifebecause insurance is one of the means to minimize losses due to disasters or catastrophes. In the implementation of itsbusiness loss insurance or sharia life applies prinsif please-help. This principle is the basic foundation in enforcing theconcept of Sharia insurance.